Microflowers of Sn-Co-S derived from ultra-thin nanosheets for supercapacitor applications. (May 2022) - Kumar, Sachin; Mir, Irshad Ahmed; Ahmad, Zubair; Hui, Kwan San; Dinh, Duc Anh; Zhu, Ling; Hui, Kwun Nam; Shim, Jae-Jin
Highlights: The novel broccoli-like 3D microflowers of Sn-Co-S are directly grown on Ni foam. The 3D architecture of microflowers is composed of ultra-thin 2D nanosheets. The optimized electrode exhibits excellent specific capacitance of 2319.3 F g -1 . The ASC device exhibits ultra-high energy density and superior cycling stability. Abstract: Herein, for the first time, we report 3D broccoli-like microflowers of Sn-Co-S directly grown on the Ni foam (Sn-Co-S/NiF) using an easy solvothermal method for the supercapacitor application. The as-fabricated Sn-Co-S/NiF electrode possesses an ultra-high specific capacitance of 2319.3 F g −1 (specific capacity of 418.7 mAh g −1 ) at 5 mA cm −2 and an outstanding rate capability of 70.3 %. The optimized Co doping, and unique architecture of the electrode may be responsible for the excellent performance of the electrode. Taking benefit from the high specific capacitance and fast charge transport properties of Sn-Co-S/NiF electrode, the fabricated asymmetric supercapacitor (ASC) exhibits a large potential window of 1.7 V and outstanding cycling stability of 95.8% after 10000 cycles. Moreover, the ASC device delivers an excellent energy density of 66.9 W h kg −1 at a power density of 560.1 W kg −1 which is substantially high as compared to recently reported ASC devices. These findings confirm the potential use of Sn-Co-S/NiF in new generation energy-storage devices. Graphical abstract: Image, graphical abstract